Childhood obesity prevention international research, controversies, and interventions - O'Dea, Jennifer A.; Eriksen, Michael P. (Oxford : Oxford University Press, 2010)
This text combines health education theory, research, and practice to guide researchers, students, educators, community health workers and practitioners in the prevention of childhood obesity and the promotion of child and adolescent health and well-being.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Obesity in children -- Prevention